Ultrasonographic evaluation of the coelomic cavity in Rhode Island Red hybrid hens (Gallus gallus domesticus). Issue 5 (11th April 2022) - Gros, Lucile; Cococcetta, Ciro; Coutant, Thomas; Gomes, Eymeric; Hahn, Harriet; Huynh, Minh
Abstract: Backyard chickens are gaining popularity, and so is individual veterinary care for their health and management. Ultrasonography represents an important part of the imaging diagnostic arsenal in veterinary medicine; however, published data on its use in chickens are scarce and mostly focus on the reproductive tract. The objectives of this prospective, reference interval study were to describe a standard protocol for a full coelomic evaluation and the normal ultrasonographic appearance and measurements of the coelomic organs in awake and anesthetized healthy hens. The liver, gallbladder, gonad, gastrointestinal tract, pancreas, and spleen were clearly visualized in 21 Rhode Island Red hybrid hens (8 immatures, 13 adults) included in this study. In all animals, there was a scant amount of coelomic fluid, which was more visible at the cardiac apex. The cysticoenteric duct and hepatoenteric duct were visualized in 57% (12/21) of the hens. Seven hens were anesthetized and placed in dorsal decubitus, as the kidneys were not visualized in the hens while standing. Reference intervals were calculated for the splenic short and long axes, proventricular wall thickness, ventricular wall thickness, and duodenal wall thickness. Reference values were measured for the thickness of the pancreas, gallbladder wall, and kidneys, as well as the diameters of the biliary ducts. Moreover, five hens of different breeds were examined, and the results obtained were comparable to those of previous studies. The results of this study support the use of ultrasonography as a diagnostic tool in Rhode Island Red hybrid hens and provide reference ranges for use in hens with clinical diseases involving coelomic organs.